Pengaruh Tingkat Pendidikan Formal terhadap Tingkat Partisipasi dalam Pemeliharaan Kesehatan Masyarakat di Dusun Massema Desa Leoran Kecamatan Enrekang Kabupaten Enrekang - Saidang Saidang; Rasman Razak; Ardiansyah Ardiansyah (JURNAL EDUKASI NONFORMAL, 2021)
This study aims to determine how much influence the level of formal education has on the level of community participation in public health maintenance in Massemba Hamlet, Leoran Village, Enrekang District, Enrekang Regency. This study uses a quantitative approach with a descriptive type of research. The number of respondents who were studied amounted to 40 people. In this study there are two variables, namely variable X (Level of Formal Education) and variable Y (Level of Community Participation in Health Care). The location of the research was carried out at the Leoran Village Office, Enrekang Regency. The subjects of this research are adults aged 25-40 years, who are active in the community and come from high school graduates to bachelor's degrees professionally with the object of research namely the influence of formal education level on the level of participation in public health care in Massemba Hamlet, Leoran Village, Enrekang District, Enrekang Regency. The data was collected using a questionnaire/questionnaire, validity and reliability, and documentation. Data analysis was carried out by several techniques, namely descriptive analysis, simple regression analysis, and t test analysis with the help of the IBM SPSS 23 computer application program. Based on the results of data analysis using statistical methods, namely simple linear regression, the coefficient of determination was 44.3% with a value of correlation coefficient of 0.639. Based on these results, it can be concluded that the level of formal education affects a person's level of participation in maintaining public health in Massemba Hamlet, Leoran Village, Enrekang District, Enrekang Regency.